O que me trouxe até aqui? diferentes jornadas do consumidor que pratica o descarte sustentável - Radtke, Manoela Lawall (2021)
Despite being considered a consumption behavior, disposal is still treated in an incipient way in consumer literature. In addition, little is know about the entire journey of those who practice sustainable consumption disposal. In order to fill this gap, this exploratory study of a qualitative nature interviewed 19 consumers who have already discarded items through return programs for recycling purposes of two products: slow fashion wallet and coffee capsule. Records of photos and videos of these consumers were also registered, in addition to the analysis of social media from the studied brands. The results allow the proposition of a disposal journey framework and the understanding of the this journey and its touchpoints for the studied products as a different trajectory. Still, it was found that detachment, the emotional and mental separation from the product, just happens in some circumstances. Theoretical, managerial and social implications of this journey of sustainable consumption disposal are discussed.